Prospective analysis of outcomes of cataract phacoemulsification with the implantation of the Crystalens accommodative intraocular lens - Starus, Michał; Wilczyński, Michał; Synder, Aleksandra; Pałenga-Pydyn, Dorota; Omulecki, Wojciech (Klinika Oczna / Acta Ophthalmologica Polonica, 2016)
Objectives : To evaluate visual outcomes after bilateral implantation of Crystalens accommodative intraocular lenses. Material and methods : The study group consisted of 20 patients (40 eyes) who underwent uneventful phacoemulsification through a 2.8 mm wide clear corneal incision followed by the implantation of an accommodative intraocular lens Crystalens HD or Crystalens AO. Uncorrected visual acuity, best corrected visual acuity, distance corrected intermediate visual acuity, distance corrected near visual acuity, best near visual acuity 1, 3, 6, 12 months postoperatively were evaluated. Distance visual acuity was measured with Snellen test. Near (40 cm) and intermediate (80 cm) visual acuity were measured with Jeager test. Results : The mean uncorrected distance visual acuity was 0.94 and 0.89 at month 1. and 12., respectively. The distance corrected intermediate visual acuity was 0.9 and 0.86 at month 1. and 12., respectively. The distance corrected near visual acuity was J1 in 10% and J3 in 50% of patients at month 1. It was J1 in 10% and J3 in 55% of patients at month 12. Conclusions : Crystalens intraocular lens implantation in our patients enabled them to achieve good distance, near and intermediate visual acuity. The majority of patients did not require spectacle correction for distance and near (87.5% and 65%, respectively). The achieved results did not differ significantly at months 1., 6., and 12. postoperatively.